Kiertotalous vaateyrityksen vastuuviestinnässä - Hjerppe, Cecilia (VAKKI ry, 2020)
Circular economy as a current topic has recently been taken up by companies in their communication about corporate social responsibility. In this article, the discursive construction of circular economy is studied in the context of a clothing company’s CSR communication. The tensions of responsible business and consumption in the fashion industry become apparent when a fast fashion company uses circular economy as a framing of sustainability and draws from a discourse of slow fashion in its CSR communication. This study sheds light on how an organization negotiates these tensions through its sustainability report and social media communication. The meaning making of circular economy is analyzed through a discourse analysis focusing on the different representations and subject positions connected to the theme. The study shows that circular economy is constructed as representations on different levels – as societal change, a business model, and a form of consumption – which position the organization as a part of change and as an enabler, while the consumer is positioned through a discourse of responsibilization.
Keywords: muotiteollisuus; vastuullinen kuluttajuus; vastuuviestintä; kiertotalous; fi=Viestintätieteet|en=Communication Studies|